PENGARUH FIKSATOR JERUK NIPIS TERHADAP PEWARNAAN ESKTRAK DAUN JAMBU BIJI DILIHAT DARI KETUAAN WARNA DAN KETAHANAN LUNTUR PENCELUPAN KAIN BATIK TULIS - Agnes Maria Chrismayani Sasana; Yasmi Teni Susiati (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2015)
This research is aimed at understanding the effect of lime fixator over the coloring of guava-leave extract observed by the maturity of color and the color fastness of the dyeing of handmade-batik fabric. The hypothesis of this research is that lime fixator affects the coloring. The data of this study are processed by Anova Kruskall Walls analysis. The result shows that, during three test, there are differences of both color maturity and fastness of fabric dyed in the temperature of 400 C, as indicated by minimum-maximum scores, mean, and standard deviation. The color-maturity has maximum score of 5, minimum score of 4, and average score of 4.33, while colour fastness has maximum score of 5, minimum score of 4, and average score of 4.33. The calculation of F-test shows that the calculated-F is 12,33>4.99 with significance level of 0.007<0.05. Since the value of calculated-F is higher than table-F, it can be concluded that there are connections between color maturity and color fastness.